Penerapan Metode Demonstrasi dalam Meningkatkan Prestasi Belajar Fikih Siswa Madrasah Ibtidaiyah - Dewi, Rachma Rusdiana; Subando, Joko (TSAQOFAH, 2025)
This study aims to examine the effectiveness of the demonstration method in improving learning achievement in Fikih subjects at Madrasah Ibtidaiyah (MI). The research is grounded in the urgency of integrating cognitive, affective, and psychomotor aspects in the teaching of worship practices such as wudu, salat, and tayammum. A descriptive qualitative approach was employed through a literature review, with data sourced from academic journals, books, and previous research findings. The results indicate that the demonstration method positively impacts students’ understanding of Fikih concepts, enhances worship skills, and fosters the development of religious character. The effectiveness of this method depends on teacher preparedness, availability of learning media, and efficient time management. However, challenges such as large class sizes and limited resources were identified. These challenges can be addressed through innovative strategies, including group-based learning and the use of simple teaching aids. The study concludes that the demonstration method is effective for Fikih instruction at MI, as it cultivates students who are not only intellectually competent but also practically skilled and morally upright. The implications of this study contribute to the development of practical and contextual Fikih learning models in Islamic primary education.